2004
DOI: 10.1103/physrevlett.93.163401
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of Interatomic Coulombic Decay in Neon Dimers

Abstract: Recently Cederbaum et al. [Phys. Rev. Lett. 79, 4778 (1997)]] predicted a new decay channel of excited atoms and molecules termed interatomic Coulombic decay (ICD). In ICD the deexcitation energy is transferred via virtual photon exchange to a neighboring atom, which releases it by electron emission. We report on an experimental observation of ICD in 2s ionized neon dimers. The process is unambiguously identified by detecting the energy of two Ne1+ fragments and the ICD electron in coincidence, yielding a clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
248
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 304 publications
(263 citation statements)
references
References 11 publications
9
248
1
Order By: Relevance
“…Figure 2(a) shows that distribution on a logarithmic color scale. Apart from the structures described in [3], a set of new features appears at higher KERs and photo electron energies that do not belong to ICD or 2s photoionization. In order to identify the origin of those features, Fig.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Figure 2(a) shows that distribution on a logarithmic color scale. Apart from the structures described in [3], a set of new features appears at higher KERs and photo electron energies that do not belong to ICD or 2s photoionization. In order to identify the origin of those features, Fig.…”
mentioning
confidence: 89%
“…Our expectation is the following. Shakeup states of even parity -just like the 2s ionized state investigated so far [2,3]-can decay to the 2p ionized ground state via virtual dipole photon emission (i.e., the dipole-allowed virtual photon exchange ICD channel is open), whereas decay from excited states of odd parity to the ionized ground state is dipole forbidden, and thus the ICD takes place only at small R where the overlap of the orbitals becomes significant. Measuring R at the instance of ICD by detecting the kinetic energy release (KER) for each shakeup state separately, we have successfully demonstrated that the dipole-allowed ICD takes place at the instant of photoionization at the equilibrium R of the ground state, whereas the dipole-forbidden ICD takes place only after shortening of R, i.e., contraction of the dimer.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…[10][11] In recent years a set of novel non-local autoionization processes has been identified to play an important role in weakly bonded atomic and molecular systems. [12][13][14] One such relaxation process is Intermolecular Coulombic Decay (ICD), initially observed upon innervalence ionization of van der Waals-bonded clusters, 12,[15][16][17] and later also (hydrogen bonded) water clusters. 18 In the ICD process, the energy provided by an outer valence electron upon filling the vacancy is used to expel a second electron from an atom or molecule neighboring the initially ionized site.…”
Section: Identifying the Initial Products Of The Interaction Of High-mentioning
confidence: 99%